Study of Antibiotic Sensitivity of Aural Swab and Aetiological Factors of Chronic Otitis Media-Active Mucosal Type - Uddin, Md Nesar; Islam, Mohammed Sirazul; Hossen, Mohammad Delwar; Alam, Mohammed Iftekharul; Hossain, Mohammad Kamal (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Chronic otitis media (COM) refers to chronic inflammation of mucoperiosteal lining of middle ear cleft resulting in aural discharge and deafness. The objective of this study is to evaluate the antibiotic sensitivity and aetiological factors of COM. Methods: This cross-sectional study was conducted from July 2017 to June 2018 for duration of one year among the patients who attended with COM- active mucosal disease at Department of ENT & Head Neck Surgry, Combined Military Hospital (CMH) Chattogram. Total 50 cases were isolated and among them 5 cases had been suffering from bilateral COM. Aural swab was taken from 55 ears and a predesigned data collection sheet was duly filled up with the information of socioeconomic status of the patient. The laboratory records of every case was systematically organized. The data were analyzed with simple manual analysis using percentage and frequency. Results: About 24% patients were in 31-40 years age group. Out of 50 patients 62% were male. 44% patient lived in barrack. Ear cleaning habit shows, 32% has got the cleaning habit with cloth and stick. Out of 50 patients 5 had bilateral COM. So out of 55 ears, Culture & sensitivity test viewed that Pseudomonas aeruginosa was the most predominant organism - 41.8% followed by S. aureus- 30.9% Antibiotic sensitivity profile shows, 80% cases showing sensitivity to Amikacin then gentamycin-73.3% Resistant 5 cases showed 100% sensitivity to Tazobactum. Again out of 19 cases of Gram positive organism 78.9% were sensitive to Amoxyclav. 3 resistant cases showed 100% sensitivity to Meropenem. Conclusion: By studying this topic we hope to able to make an idea about the aetiological and predisposing factors and antibiotic sensitivity of COM-active mucosal variety. Bangladesh J Otorhinolaryngol 2021; 27(2): 111-116